2009
DOI: 10.1021/jo900823h
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the Kulinkovich Cyclopropanation of Nitriles

Abstract: The stereochemistry of the Kulinkovich cyclopropanation of nitriles with alkenes has been examined by employing (E)-disubstituted alkenes and deuterium-labeled homoallylic alcohols as a stereochemical probe. An intramolecular cyclopropanation proceeds with preservation of the olefin configuration. On the other hand, intermolecular counterparts occur with both preservation and reversal of the olefin configuration, which corresponds to retention and inversion of configuration at the Ti–C bond, respectively, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…25 Following this seminal work, Cha further revealed that both retention and inversion of configuration at the Ti-C bond occurred in intermolecular coupling between a homoallylic alcohol and a nitrile. 26 In the event of asymmetric cyclopropanation with alkoxide 13-d, the formation of diastereomeric cyclopropanols 1c-d and 1c-d′ could be expected as a result of retention or inversion of configuration at Ti-C bond respectively (Scheme 4). It is remarkable that both diastereomers 1c-d and 1c-d′ must behave as a pair of enantiomers during HPLC analysis with a chiral column, since isotopic substitution cannot strongly affect retention times.…”
Section: Feature Syn Thesismentioning
confidence: 99%
“…25 Following this seminal work, Cha further revealed that both retention and inversion of configuration at the Ti-C bond occurred in intermolecular coupling between a homoallylic alcohol and a nitrile. 26 In the event of asymmetric cyclopropanation with alkoxide 13-d, the formation of diastereomeric cyclopropanols 1c-d and 1c-d′ could be expected as a result of retention or inversion of configuration at Ti-C bond respectively (Scheme 4). It is remarkable that both diastereomers 1c-d and 1c-d′ must behave as a pair of enantiomers during HPLC analysis with a chiral column, since isotopic substitution cannot strongly affect retention times.…”
Section: Feature Syn Thesismentioning
confidence: 99%
“…The first step would imply the insertion of the nitrile moiety of 3 into the titanacyclopropane intermediate A (obtained from Ti(OiPr) 4 and 2 equiv of EtMgBr) to provide the five-membered titanacycle C. The diketone 5 might be directly obtained from an intramolecular direct insertion of the ester C=O bond into the remaining titanium-carbon bond, however this possibility is unlikely because of obvious geometric constrictions. [17][18][19] For instance, the addition of Grignard reagents to five-membered oxatitanacyclopentanes has been proposed by Kulinkovich et al to explain the need for excess Grignard in the synthesis of cyclopropanols. Several related metallacycle ring-openings have already been proposed in the literature.…”
mentioning
confidence: 99%
“…Several related metallacycle ring-openings have already been proposed in the literature. [18] The Table 1, entry 4). [17] Recently, the azatitanacyclopent-2-ene ring-opening has been postulated by Cha et al to explain the nonselective cyclopropanation of nitriles.…”
mentioning
confidence: 99%
See 2 more Smart Citations